(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency of Hepatitis B and Hepatitis C in Hazara population of Quetta. Patients and Methods: This was a cross-sectional prevalence study conducted in the Marryabad area of Quetta. Total of 3000 volunteers were enrolled who fulfilled the following criteria: all participants were of Hazara ethnicity, they were permanent residents of Marryabad Quetta city, ages 2 years to 60 years. The following subjects were excluded from this study: non Hazara ethnicity, people below 2 years and above 60 years of age, non-residents of Quetta city. Two-stage cluster sampling technique was employed to draw required sample based on voting lists. Trained health workers were deployed in each sample unit at a time for collecting the sample and required data and filling the questionnaire. The collected samples were centrifuged within 6 hours of collection and serology for anti-HCV and HBsAg was performed on the collected blood samples using enzyme linked immunosorbent assay. Results: Overall 247 (8.23%) were positive for HBs Ag with male to female ratio of 5:8 and the mean age was 43.47 ± 14.22. 420(14%) had positive anti-HCV with the mean age of 35.04 ± 16.77 and male to female ratio of 3:4.Following were the positive percentage of for HBsAg according to professions: Doctors (0.13%) (RR 1.2498; 95% CI 0.4901 to 3.1871) P = 0.6407, Nurses and Paramedics (0.10%)(RR: 1.4631; 95% 0.5027 to 4.2584) P = 0.4850, Barbers and quack(0.17%) (0.7446; 95% 0.3158 to 1.7553)P = 0.5002. Following percentages were positive for anti-HCV: Doctors (0.27%) (1.4742; 95%CI 0.7897 to 2.7522) P = 0.2230, Nurses and Paramedics (0.2%) (1.7246; 95%CI0.8536 to 3.4844) P = 0.1288, Barbers and quack (0.57%) (1.5202; 95%CI 0.9867 to 2.3420) P = 0.0575. Conclusion: Hepatitis B and C remain a significant problem in the Hazara community and in certain professions at risk.